Multimodal Presentation in Academic Writing and Rhetoric: Balancing Persuasion and Interest - Kalynovska, Iryna (Харківський національний університет імені В.Н. Каразіна, 2024)
The use of multimodal presentation in academic writing and rhetoric is gaining prominence due to its potential to balance persuasion and interest. This approach involves composing across different media, allowing students to engage with diverse semiotic resources to create persuasive and engaging multimodal texts (Gagich, 2020).
This study aims to explore the impact of multimodal presentation on university student engagement and the development of persuasive presentation skills with potential applications in teaching academic writing and rhetoric course to Foreign Philology Faculty students. The research questions include: How does multimodal presentation assignment challenge university students to consider rhetorical appeals and develop oral presentation skills? What is multimodal presentation influence on university student engagement and the development of persuasive oral presentation skills?
Keywords: multimodal presentation; мультимодальна презентація; academic writing and rhetoric; академічне письмо і риторика; persuasion; переконання; intrest; зацікавленість; 81(082)